Manufacturing method of electric contact material for magnetic latching field based on electric spark sintering technology

Through the optimization of electric spark sintering technology and process, the pores and looseness problems in electrical contact materials are solved, the density and performance of the materials are improved, the electrical life is extended, and the reliability of electrical equipment is improved.

CN119464814APending Publication Date: 2025-02-18ZHEJIANG FUDA ALLOY MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411567338.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

There are problems such as pores and looseness in existing electrical contact materials, which leads to unqualification in subsequent wire processing or electronic devices, affecting the reliability of electrical equipment.

Method used

The production methods based on electric spark sintering technology are adopted, including powder mixing, isostatic pressure, electric spark sintering, repressing, hot extrusion and forming steps, and the compactness and performance of the material are improved by optimizing the formulation and process conditions of AgSnO2 alloy.

Benefits of technology

It achieves improvement of internal density of materials, reduces holes and loosening problems, improves the mechanical and physical properties of electrical contact materials, extends the electrical life, and improves the reliability of electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464814A_ABST
    Figure CN119464814A_ABST
Patent Text Reader

Abstract

A manufacturing method of an electric contact material for the magnetic latching field based on the electric spark sintering technology comprises the following steps that (1) powder mixing is conducted, specifically, according to the formula of AgSnO2 alloy, 200-mesh and 300-mesh silver powder, SnO2 powder and additive powder are mixed through a plough blade type powder mixing machine, and the powder mixing time is set to be 2-6 h; (2) isostatic pressing: forming the AgSnO2 powder obtained in the step (1) into a cylindrical spindle by using an isostatic pressing machine; (3) electric spark sintering is conducted, specifically, the ingot manufactured in the step (2) is put into electric spark sintering equipment to be sintered; (4) re-pressing: putting the AgSnO2 spindle obtained in the step (3) into a four-column hydraulic press for re-pressing; (5) hot extrusion is conducted, specifically, the cylindrical billet obtained in the step (4) is molded into an AgSnO2 wire material through a hot extrusion process; and (6) forming is conducted, specifically, the obtained AgSnO2 wire is subjected to hot drawing machining to obtain a finished product, and the finished product is formed into the electrical contact rivet through a cold heading method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing an electric contact material used in the magnetic retention field based on an electric spark sintering technology, and belongs to the field of electrical material manufacturing. Background Art

[0002] In the field of electrical contact materials, silver cadmium oxide was widely used in various relays in the early years because of the arc extinguishing advantage brought by the volatilization of cadmium oxide components at high temperatures. However, in recent years, under the requirements of international environmental protection directives, the application of this material has begun to be restricted in many places, and practitioners have begun to develop other electrical contact materials that meet environmental protection requirements. Silver tin oxide is one of the most widely used environmentally friendly materials in recent years. 2 The main methods include alloy internal oxidation method, atomization method and powder metallurgy method. The electrical contact materials made by powder metallurgy process have problems such as pores and looseness, which lead to unqualified phenomena in subsequent wire processing or use of electronic devices, which has a great impact on the reliability of electrical equipment.

[0003] Through the relevant literature search, the patent literature retrieved for preparing silver tin oxide materials is as follows:

[0004] The Chinese patent with the publication number CN11058816A discloses a method for preparing a contact material for a high-voltage DC relay, which belongs to the technical field of powder metallurgy material preparation. Through two pressing and two sintering, the first pressing is first formed into a blank, and the material stress is removed after the initial firing to reduce the deformation strength; the purpose of the second pressing is to perform shaping to reach the final product size and reduce the subsequent machining process. The second re-firing can improve the mechanical strength and material toughness of the material, which is beneficial to the service life of the material. The product requires a mechanical life of one million times, so secondary sintering is required to improve the material strength; the present invention is a newly developed method for preparing a contact material for a high-voltage DC relay, which has a simple process, low cost, and high-performance point material for a high-voltage DC relay. While meeting the performance requirements, it has a high cost-effectiveness ratio and can replace the current pure copper contacts, greatly improving the reliability of the high-voltage DC relay. However, it still cannot solve the problems of holes and looseness inside the electrical contact material.

[0005] In the traditional process of preparing silver tin oxide materials, the problem of combining tin oxide particles with the silver matrix in the powder metallurgy process cannot be solved, and the prepared materials still have certain voids and looseness. As a result, mass production cannot be achieved and the electrical life of the final electrical products is poor. Therefore, it is necessary to improve the existing electrical contact material manufacturing process. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for manufacturing an electrical contact material for use in the field of magnetic retention based on the electric spark sintering technology.

[0007] A method for manufacturing an electric contact material for magnetic retention based on electric spark sintering technology, comprising the following steps:

[0008] (1) Mixed powder: According to AgSnO 2 The alloy formula is 200 mesh 300 mesh silver powder, SnO 2 Powders and additive powders are mixed using a ploughshare mixer, and the mixing time is set to 2-6 hours;

[0009] (2) Isostatic pressing: The AgSnO 2 The powder is formed into cylindrical ingots using an isostatic press;

[0010] (3) electric spark sintering: placing the ingot prepared in step (2) into an electric spark sintering device for sintering;

[0011] (4) Repressing: The AgSnO 2 The spindles are placed in a four-column hydraulic press for re-pressing;

[0012] (5) Hot extrusion: The cylindrical ingot obtained in step (4) is formed into AgSnO by hot extrusion process. 2 Wire;

[0013] (6) Molding: The obtained AgSnO 2 The wire is hot drawn into the finished product and then formed into electrical contact rivets using cold heading.

[0014] Preferably, in step (1), the Ag, SnO 2 The components of the additives are calculated by weight percentage: Ag 75-92%, Sn 7.5-23%, and additives 0.5-2%.

[0015] The high silver content (75-92%) makes the material have excellent conductivity. The conductivity of silver is better than other metals, which can meet the requirements of electrical contact materials for good conductivity and ensure the effective transmission of current. The appropriate addition of tin (7.5-23%) provides the alloy with good weldability and plasticity, so that the material has better forming ability in processing and application, meeting the needs of different usage scenarios. The appropriate amount of additives (0.5-2%) can not only improve the high temperature performance and oxidation stability of the material, but also effectively improve the wear resistance of the material and enhance the service life of the electrical contact parts. This composition ratio can achieve stable performance of the material under different electrical loads, especially the adaptability to fast switching and high-frequency applications, so that it can maintain good contact quality under extreme conditions. By controlling the ratio of Ag and Sn, the performance of the alloy can be avoided due to phase changes during use, thereby ensuring the reliability and stability of the electrical contacts in long-term use. The appropriate composition configuration balances the performance and cost of the material, reduces the excessive dependence on high-cost silver, while maintaining the high-quality performance of the product, which helps to reduce the overall production cost. The optimization of the combination ratio enables this alloy material to exhibit better oxidation resistance and corrosion resistance under different environmental conditions (such as humidity, temperature, etc.), and achieves a wider range of applications. Through scientific proportioning, the best comprehensive performance can be achieved, which not only improves conductivity, but also ensures the wear resistance, high temperature resistance and stability of the material, and meets practical application needs in all aspects.

[0016] Preferably, in step (1), the additive is one or more of indium oxide, copper oxide, aluminum oxide, and lanthanum oxide.

[0017] These oxides can improve the AgSnO 2 The electrical conductivity and thermal stability of the alloy. Indium oxide can improve the electrical conductivity of the material, while aluminum oxide and lanthanum oxide can improve the high temperature resistance and mechanical strength of the material. The addition of copper oxide can not only improve the conductivity of the material, but also enhance the wear resistance, so that the electrical contacts have a longer service life in frequent operations and reduce the cost of frequent replacement. Additives help improve the fluidity and dispersibility of the powder during the mixing process, thereby improving the mixing uniformity and avoiding finished product defects caused by uneven materials. The introduction of oxides can further optimize AgSnO by changing the crystal structure of the material. 2 The microscopic properties of AgSnO can improve the stability of the overall structure. In high temperature environments, these oxides can effectively prevent silver and tin from oxidizing, improve the stability and performance of the material under harsh conditions, and adapt to a wider range of application scenarios. 2Produce synergistic effects and enhance the overall properties of the material. For example, lanthanum oxide can promote interfacial reactions and increase the bonding strength of the material. For certain specific applications, the conductivity and thermal conductivity of the material in electrical contact can be specifically improved by optimizing the type and proportion of additives, thereby improving its use efficiency.

[0018] Furthermore, in step (2), the isostatic press uses a pressure of 100-300 MPa and a holding time of 40-160 s.

[0019] The appropriate pressure range and holding time can promote the uniform densification of powder materials during the molding process, ensure that the microstructure of the ingot is more uniform, thereby improving the overall strength and stability of the material. Under high pressure conditions, the contact between powder particles is closer, which can effectively reduce the voids and defects generated during the molding process and improve the geometric dimensional accuracy and shape consistency of the finished product, which is crucial for subsequent processing steps. After treatment with appropriate pressure and time, the compressive strength and wear resistance of the ingot can be significantly improved, and its stability and durability during subsequent sintering and processing can be increased. Applying a higher static pressure helps to reduce the porosity in the powder, reduce the defect rate of the final product, and improve the density of the material through the rearrangement of the material and the mutual densification between the particles. During the holding process, the particles will undergo plastic deformation and reshape the microscopic interface, which will enhance the bonding force between the particles, improve the bonding effect during the sintering process, and optimize the performance of the ingot. The appropriate holding time allows the powder to remain under pressure for a sufficient time to achieve optimal densification and interaction, greatly improving the sintering quality of the material during the subsequent sintering process. The pressing conditions can be verified through theoretical calculations and a large amount of experimental data to ensure their operability and stability in practical applications, facilitating their promotion in industrial production.

[0020] Preferably, in step (3), the electric spark sintering equipment is set to a sintering temperature of 500-800°C, oxygen is introduced, the pressure is 0.6-3.0 MPa, the sintering time is 1-5h, and the current is 1000-5000A.

[0021] Through high current (1000-5000A) electric spark sintering, strong local heat can be generated in a short time, prompting the particles to reorganize quickly and achieve a reasonable crystal structure, which helps to reduce the grain size of the material and improve the overall material properties. Moderate sintering temperature (500-800℃) can effectively promote Ag-SnO 2Densification of materials improves the density of materials, enhances their mechanical strength and durability, and improves their overall performance. The setting of introducing oxygen can effectively prevent silver and tin from oxidizing at high temperatures, maintain the integrity of the materials, and promote the formation of certain oxides in the materials, ultimately improving the chemical stability of the materials in high temperature environments. Appropriate pressure (0.6-3.0MPa) and sintering time (1-5 hours) can ensure full contact between the particles, form excellent interface bonding, improve electrical conductivity, and meet the needs of various electrical applications. The high current during the sintering process can bring a faster reaction rate, ensure that the internal structure of the formed material is uniform, avoid local defects caused by uneven temperature and environment, and thus improve the consistency of the product. Reasonable sintering conditions can significantly improve the wear resistance and oxidation resistance of composite materials, improve the operating stability of electrical contacts under high frequency and high load conditions, and extend the service life of components.

[0022] Preferably, in step (4), the four-column hydraulic press is set to a pressure of 50-200 MPa and a pressure holding time of 10-50 s.

[0023] Appropriate high pressure (50-200MPa) can further compact the microstructure of the sintered material and reduce the porosity, thereby significantly enhancing the density of the material and improving its mechanical strength and wear resistance. The holding time (10-50 seconds) fully allows the material to be microscopically rearranged under high pressure, promotes better bonding between particles, improves the microscopic uniformity of the material, and reduces internal defects. By enhancing the tightness of the internal structure of the material, its compressive strength and fatigue resistance can be effectively improved, so that the final product has better stability and reliability in various applications. Under appropriate pressure and holding time, the brittleness of the material can be reduced, its ductility can be improved, and the electrical contact can meet higher operating dynamic requirements. This pressing process can make the material easier to form, reduce the difficulty of subsequent processing, effectively improve production efficiency, reduce material waste, and maximize economic benefits. With the flexible adjustment of the holding time, the characteristics of the final product can be flexibly controlled according to the specific characteristics of the material and application requirements, so that the final product is more adaptable to various environments and load conditions. In a high-pressure environment, the material's lattice defects and stresses are relaxed, helping to achieve a slight "annealing" effect, further improving the material's stability and durability.

[0024] The beneficial effects of the present invention are as follows: by using electric spark sintering technology, the tin oxide particles are more tightly combined with the silver matrix, the prepared wire has good mechanical properties and physical properties, can eliminate the poor combination of different components in the traditional sintering process, the abnormalities such as shrinkage holes inside the material, etc., excellent processing performance, and better electrical life in high-current magnetic latching relays. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0026] Figure 1 It is a flow chart of the manufacturing method of the present invention. DETAILED DESCRIPTION

[0027] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0028] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. The subsequent embodiments will not explain this one by one.

[0029] The directions and positions mentioned in the present invention, such as "upper", "lower", "front", "back", "left", "right", "inside", "outside", "top", "bottom", "side", etc., are only for reference to the directions or positions of the drawings. Therefore, the directions and positions used are for explaining and understanding the present invention, but not for limiting the scope of protection of the present invention.

[0030] See also Figure 1 The present invention provides an embodiment of a method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology, comprising the following steps:

[0031] (1) Mixed powder: According to AgSnO 2 The alloy formula is 200 mesh 300 mesh silver powder, SnO 2 Powders and additive powders were mixed using a shovel mixer, and the mixing time was set to 2-6h. Ag75wt.%, SnO 2 23wt.%, additive 2wt.%, mixing time is set to 2-6h;

[0032] (2) Isostatic pressing: The AgSnO 2 The powder was formed into cylindrical ingots using an isostatic press with an operating pressure of 260 MPa and a holding time of 100 s.

[0033] (3) Electric spark sintering: The ingot prepared in step (2) is placed in an electric spark sintering device for sintering, the sintering temperature is set to 600° C., oxygen is introduced, the pressure is 1.2 MPa, the sintering time is 2 hours, and the current is 2000 A;

[0034] (4) Repressing: The AgSnO 2 The spindle is placed in a four-column hydraulic press for re-pressing, the pressure is set to 200 MPa, and the holding time is 30 seconds;

[0035] (5) Hot extrusion: The cylindrical billet obtained in step (4) is formed into AgSnO 2 Wire;

[0036] (6) Molding: The obtained AgSnO 2 Wire hot drawing process The finished product is formed into electrical contact rivets using cold heading.

[0037] Embodiment 2:

[0038] The difference from Example 1 is that the raw material content is different. It is configured according to 10 kg per time, and the input formula ratio is Ag85wt.%, SnO 2 13wt.%, additive 2wt%.

[0039] Embodiment 3:

[0040] The difference between Example 1 and Example 2 is that the raw material content is different, and the raw material content is 10 kg per time, wherein Ag is 90 wt.%, SnO 2 9wt.%, additive 1wt%.

[0041] The above method is used to make AgSnO 2 / Cu rivet contacts were used for simulated electrical performance experiments. The rivet specifications were R5.2x1.5(0.5)+3.5x1.2SR15 for the moving contact and F5.2x1.5(0.5)+3.5x1.2 for the static contact. The simulated electrical performance experiment conditions were as follows: 250VAC, 90A, resistive load, contact frequency 30 times / minute;

[0042] The experimental results are shown in Table 1.

[0043] Table 1 Parameter settings and test results of different embodiments and comparative examples

[0044]

[0045] Using a plowshare mixer in the powder mixing step can ensure that the silver powder, SnO 2The uniform mixing of powder and additives helps to achieve structural consistency in the subsequent molding process and improve the performance of the material. The mixed powder is molded into a cylindrical ingot through isostatic pressing, which can make the ingot have uniform density and structure, improve the quality of the subsequent sintering process, and ensure the mechanical strength and conductive properties of the material. The electric spark sintering technology can sinter the ingot at a higher temperature in a shorter time, effectively promoting the densification of the powder material and improving the AgSnO 2 The conductivity and wear resistance of the material are improved, while reducing the oxidation and sintering defects of the particles. The use of a four-column hydraulic press for re-pressing in the re-pressing step helps to further improve the density of the material and optimize the microstructure, thereby enhancing the compressive strength and service life of the finished product. The hot extrusion process can effectively improve the plasticity of the material, making AgSnO 2 The process of processing the billet into wire is smoother, reducing the breakage and defects of the material during the forming process. Through the final steps of hot drawing and cold heading, high-precision and high-consistency electrical contact rivets can be obtained, ensuring the reliability and stability of the final product during use, meeting the high performance requirements of magnetic holding devices. The process flow of this method is suitable for the production of electrical contact materials of various specifications and sizes, making the material have good market adaptability and versatility. The overall production process flow is reasonably designed, which can reduce production costs, improve production efficiency, and create good conditions for industrial applications.

[0046] The present invention uses the electric spark sintering process to prepare AgSnO 2 The tin oxide particles in the material are tightly combined with the silver matrix without obvious looseness. The material density is higher than that of existing process materials. No problems such as breakage occur during the wire processing. The final rivet-shaped contacts have high density, thus having a longer electrical life in the field of magnetic holding relays.

[0047] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

[0048] Although the invention has been described with reference to several specific embodiments, it should be understood that the invention is not limited to the specific embodiments disclosed. The invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

Claims

1. A method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology, characterized in that: The steps include: (1) Powder mixing: According to the formula of AgSnO2 alloy, 200 mesh 300 mesh silver powder, SnO2 powder and additive powder are mixed using a shovel type powder mixer, and the mixing time is set to 2-6 hours; (2) Isostatic pressing: The AgSnO2 powder obtained in step (1) is formed into a cylindrical ingot using an isostatic press; (3) electric spark sintering: placing the ingot prepared in step (2) into an electric spark sintering device for sintering; (4) Re-pressing: placing the AgSnO2 ingot obtained in step (3) into a four-column hydraulic press for re-pressing; (5) hot extrusion: forming the cylindrical ingot obtained in step (4) into AgSnO2 wire by hot extrusion process; (6) Forming: The obtained AgSnO2 wire is hot-drawn into a finished product, and then formed into an electrical contact rivet using a cold heading method.

2. The method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology according to claim 1, characterized in that: In step (1), the composition of Ag, SnO2 and additives is calculated by weight percentage: Ag 75-92%, Sn 7.5-23%, and additives 0.5-2%.

3. The method for manufacturing an electrical contact material for magnetic retention based on the electric spark sintering technology according to claim 1 or 2, characterized in that: In step (1), the additive is one or more of indium oxide, copper oxide, aluminum oxide, and lanthanum oxide.

4. The method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology according to claim 1, characterized in that: In step (2), the isostatic press uses a pressure of 100-300 MPa and a holding time of 40-160 s.

5. The method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology according to claim 1, characterized in that: In step (3), the electric spark sintering equipment is set to a sintering temperature of 500-800°C, oxygen is introduced, the pressure is 0.6-3.0MPa, the sintering time is 1-5h, and the current is 1000-5000A.

6. The method for manufacturing an electrical contact material for magnetic retention based on electric spark sintering technology according to claim 1, characterized in that: In step (4), the four-column hydraulic press is set to a pressure of 50-200 MPa and a holding time of 10-50 s.